Citrus sinensis leaf petiole and blade colonization by Xylella fastidiosa: details of xylem vessel occlusion (Scientia Agricola, 2009)
Citrus variegated chlorosis (CVC), caused by Xylella fastidiosa, is an important disease of citrus in Brazil. X. fastidiosa is restricted to xylem vessels of plants and knowledge regarding xylem colonization is still limited. Our goal was to verify how this bacterium colonizes and spreads within xylem vessels of sweet orange Citrus sinensis cv. Pêra. Petioles and pieces of leaf blades from naturally infected plant exhibiting characteristic symptoms were prepared for light microscopy (LM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and immunogold labeling (IGL). Petioles from healthy plants were used as control. IGL results, using an antibody against wall hemicelluloses, revealed that the pit membrane of vessels was altered. Bacterial cells were observed in the pit between adjacent vessels. Results support the contention that X. fastidiosa produces cellulases to reach adjacent vessels. SEM revealed that colonization of sweet orange started with X. fastidiosa cells attaching to the xylem wall, followed by an increase in the number of bacterial cells, the production of fibrous material, and finally vessel occlusion by biofilm composed of copious amounts of amorphous material, strands and cells. Phenolic materials, hyperplasia and hypertrophy were noticed in leaves with gummy material. Xylem vessels frequently contained an unknown needle-like, crystallized matter blocking the vessel.